Widespread association of ERα with RMRP and tRNA genes in MCF-7 cells and breast cancers - Malcolm, Jodie R.; Leese, Natasha K.; Lamond-Warner, Philippa I.; Brackenbury, William J.; White, Robert J. (Gene, 2022)
•Estrogen receptor (ER) interacts with hundreds of tRNA genes (tDNAs) in MCF-7 cells.•Hundreds of tDNAs are also targeted in primary breast tumours and metastases.•Canonical estrogen response element is not found near top tDNA targets of ER.•ER also targets non-coding breast cancer driver gene RMRP.•ER also targets RN7SL1 gene that promotes breast cancer progression. tRNA gene transcription by RNA polymerase III (Pol III) is a tightly regulated process, but dysregulated Pol III transcription is widely observed in cancers. Approximately 75% of all breast cancers are positive for expression of Estrogen Receptor alpha (ERα), which acts as a key driver of disease. MCF-7 cells rapidly upregulate tRNA gene transcription in response to estrogen and ChIP-PCR demonstrated ERα enrichment at tRNALeu and 5S rRNA genes in this breast cancer cell line. While these data implicate the ERα as a Pol III transcriptional regulator, how widespread this regulation is across the 631 tRNA genes has yet to be revealed. Through analyses of ERα ChIP-seq datasets, we show that ERα interacts with hundreds of tRNA genes, not only in MCF-7 cells, but also in primary human breast tumours and distant metastases. The extent of ERα association with tRNA genes varies between breast cancer cell lines and does not correlate with levels of ERα binding to its canonical target gene GREB1. Amongst other Pol III-transcribed genes, ERα is consistently enriched at the long non-coding RNA gene RMRP, a positive regulator of cell cycle progression that is subject to focal amplification in tumours. Another Pol III template targeted by ERα is the RN7SL1 gene, which is strongly implicated in breast cancer pathology by inducing inflammatory responses in tumours. Our data indicate that Pol III-transcribed non-coding genes should be added to the list of ERα targets in breast cancer.